Detection of Constellation-Modulated Wireless Covert Channel Based on Adjusted CNN Model. (7th June 2021) - Huang, Shuhua; Liu, Weiwei; Liu, Guangjie; Dai, Yuewei; Bai, Huiwen
Abstract : With the development of wireless communication technology, more and more information leakage is realized through a wireless covert channel, which brings great challenges to the security of wireless communication. Compared with the wireless covert channel on the upper layer, the wireless covert channel based on the physical layer (WCC-P) has better concealment and greater capacity. As the most widely used scheme of WCC-P, the wireless covert channel with the modulation of the constellation point (WCC-MC) has attracted more and more attention. In this paper, a deep learning scheme based on amplitude-phase characteristics is proposed to detect and classify the WCC-MC scheme. We first extract the amplitude and phase characteristic of error vector magnitude (EVM) and constellation points and then map the amplitude and phase characteristic to the grayscale image, respectively. Finally, the generated feature images are trained, detected, and classified with the adjusted convolution neural network. The experimental results show that the detection accuracy of our proposed scheme can reach 98.5%, and the classification accuracy can reach 81.7%.